Platelets: a potential role in chronic respiratory diseases?. (15th September 2021) - Chebbo, Mohamad; Duez, Catherine; Alessi, Marie C.; Chanez, Pascal; Gras, Delphine
Platelets are small anucleate cells known for their role in haemostasis and thrombosis. In recent years, an increasing number of observations have suggested that platelets are also immune cells and key modulators of immunity. They express different receptors and molecules that allow them to respond to pathogens, and to interact with other immune cells. Platelets were linked to the pathogenesis of some inflammatory disorders including respiratory diseases such as asthma and idiopathic pulmonary fibrosis. Here, we discuss the involvement of platelets in different immune responses, and we focus on their potential role in various chronic lung diseases. In addition to their essential role in haemostasis and thrombosis, platelets are strong modulators of different immune responses, and could be involved in the physiopathology of several chronic airway diseases https://bit.ly/3cB6Xnj